"Credit Risk and Credit Rationing": Comment - Catt, A. J. L. (Quarterly Journal of Economics, 1963)
Journal Article “Credit Risk and Credit Rationing”: Comment Get access A. J. L. Catt A. J. L. Catt New Zealand Institute of Economic Research, Inc., Wellington, New Zealand Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 77, Issue 3, August 1963, Pages 505–510, https://doi.org/10.2307/1879576 Published: 01 August 1963